VOICES AND FOG: NARRATIVE ARCHITECTURE AND FRAGMENTED MEMORY IN UN PIANISTA ENTRE LA NIEBLA - Medina, Manuel Fernando (Universidad-Verdad, 2025)
This article presents a contemporary reading of Un pianista entre la niebla (2016) by Raúl Serrano Sánchez to examine how the novel interweaves memory, affect, and perception within an unstable narrative framework. The discussion draws on postclassical narratology, memory studies, and affective and cognitive approaches to narrative (Fludernik; Caracciolo and Kukkonen; Meretoja; Landsberg; Hutton; recent neurocognitive research). The analysis reveals that fragmentation, temporal disruption, and enunciative instability shape a narrative experience driven by embodied perception, affective persistence, and sensory residues. Figures such as Purificación and Mademoiselle Satán function as affective surfaces that activate grief, desire, and evocation. Fog operates as both a perceptual regime and a structuring principle, shaping the dynamics of memory. The novel frames memory as a non- subsumptive narrative practice and advances a poetics of instability that turns narration into an aesthetic exploration of fractured consciousness.